The role of intellectual capital in building a competitive advantage by enterprises from the transport, shipping and logistics industry (TSL) - Michal Igielski (Institute of Economic Research (IER), 2017)
The modern economy is characterized by use changes. They appear very quickly and unexpectedly. This is a situation which impedes the functioning of companies and it is a challenge for the people managing them. They have to meet new challenges and adapt to changing competitive conditions, which are associated with the processes of globalization and knowledge-based economy. Therefore, the aim of this article is to define the role of intellectual capital in companies with TSL branch in building competitive advantage. In addition, the author attempts to assess the facts of intellectual capital management in the surveyed enterprises and it will identify the barriers that accompany this process. Founded research objectives will be realized an analysis of available sources of theoretical and conducted by the author, in 2016 (100 companies with TSL from Baltic Sea Region). The study was prepared as a general survey, which describes the company and individual interviews conducted with representatives of the boards of companies and their managers (for a total of 400 people). After analyzing all the material you see the role of intellectual capital in building a competitive advantage in the surveyed entities. Especially in activities related to the improvement of the quality of services / products and the efficiency of employees. It also turned out that business owners know how important it is for them the capital and they also know the barrier implementation of this concept - the main are: the capital is not their property.
Keywords: D41; D83; L10; M12; O15; O34; 330; intellectual capital; logistics; shipping and transport industry (TSL); competitive advantage